The protective role of breastfeeding in multiple sclerosis: Latest evidence and practical considerations - Collorone, Sara; Kodali, Srikirti; Toosy, Ahmed T. (Frontiers in Neurology, 2023)
The protective role of pregnancy in multiple sclerosis (MS) has been known for decades. Conversely, there has been rich debate on the topic of breastfeeding and disease activity in MS. In clinical practice, women are often offered to resume their disease-modifying drug (DMD) soon after delivery to reduce their relapse risk. Furthermore, limited information about DMD safety during breastfeeding meant many women choose not to breastfeed, despite the World Health Organization's recommendation to breastfeed children for the first six months of life exclusively. New evidence is emerging about the protective role of exclusive breastfeeding on relapse rate. Research studies shed light on the hormonal and immunological mechanisms driving the risk of relapses during pregnancy and postpartum. Finally, case reports, real-world data, and clinical trials are increasing our knowledge of the safety of DMDs for the fetus and infant. While some DMDs must be avoided, others may be considered in highly active pregnant or lactating women with MS. This mini-review is intended to convey recent evidence supporting the protective role of exclusive breastfeeding in MS and offer clinicians practical considerations for a patient-tailored approach.